SALT AND WATER RECOVERY FROM A MIXTURE OF SALT SOLUTION THROUGH MEMBRANE DISTILLATION-CRYSTALLIZATION - ABD MAJID, NAJWA (2021)
Membrane distillation-crystallization is an emerging alternative for sustainable management of highly concentrated brine solution of water sources such as seawater, industrial wastewater and produced water. Membrane distillation-crystallization combines two individual processes of stand-alone membrane distillation system and stand-alone crystallization system in a single reactor to facilitate the extraction of clean water and separation of high purity salt contents from a brine solution.